.5x-.7=6.3

Simple and best practice solution for .5x-.7=6.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5x-.7=6.3 equation:


Simplifying
0.5x + -0.7 = 6.3

Reorder the terms:
-0.7 + 0.5x = 6.3

Solving
-0.7 + 0.5x = 6.3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.7' to each side of the equation.
-0.7 + 0.7 + 0.5x = 6.3 + 0.7

Combine like terms: -0.7 + 0.7 = 0.0
0.0 + 0.5x = 6.3 + 0.7
0.5x = 6.3 + 0.7

Combine like terms: 6.3 + 0.7 = 7
0.5x = 7

Divide each side by '0.5'.
x = 14

Simplifying
x = 14

See similar equations:

| -73=-8+5p | | 10y+4x=20 | | 5n^2-36n+57=0 | | 159=5(7+4n)+4 | | 9p-9=2(2p+8) | | 20=7-x | | -256=8(7b-4) | | 28=3w+4w | | 6x-27=17 | | 6x+4=-92 | | x^4-60+2x^2=-2x^4-x^2 | | 23=3w+4w | | 5(2d+3)=45 | | 5x+14=79 | | 4+9=2 | | 4(3)-3n=12 | | 6c-13d-9c+5d= | | x^2+Y^2-6x+4y+13=0 | | 1 = q2 | | 18y-22=3x-2 | | 12x-3x*2=0 | | 12r+s+18r+19s= | | 3v-4=3v+7 | | 11x-(7+5x)= | | 17x-8=81 | | -8(5r+1)=32 | | (-8x+2)+(-10x-7)= | | 2x-31=3(x-2) | | X^2+(6k+4)X+3=0 | | 6+30x=20x+24 | | 48*64=12x*16x | | 50-3s=2 |

Equations solver categories